2006
DOI: 10.1002/dvdy.20988
|View full text |Cite
|
Sign up to set email alerts
|

The initial fetal human retinal vasculature develops by vasculogenesis

Abstract: There is increasing evidence that the hemangioblast, a common progenitor for hematopoietic cells and endothelial cells, participates in embryonic and extra-embryonic vasculogenesis in some organs. Whether resident angioblasts or endothelial progenitor cells (EPCs) contribute to human retinal vasculogenesis is still a matter of controversy. To address this controversy, fetal human retinas of 6 -23 weeks gestation (WG) were examined using immunohistochemistry and a panel of antibodies against endothelial cell ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 44 publications
(52 reference statements)
3
64
1
Order By: Relevance
“…A further interesting phenotype identified in SDF-1/CXCR4 knockout mice is a deficiency in blood vessel development, initially observed in the gastrointestinal system (Tachibana et al, 1998). Consistent with such observations, CXCR4 receptors have been shown to be expressed by hemangioblasts, the earliest common precursor to hematopoietic and endothelial stem cells found in yolk sac blood islands (McLeod et al, 2006) and also by endothelial cells that can be derived from embryonic stem cells (ESCs) in culture (Chen et al, 2007). In the latter case these endothelial cells expressed CXCR4 and migrated towards an SDF-1 gradient.…”
Section: Development Of Non Neuronal Tissuesmentioning
confidence: 66%
“…A further interesting phenotype identified in SDF-1/CXCR4 knockout mice is a deficiency in blood vessel development, initially observed in the gastrointestinal system (Tachibana et al, 1998). Consistent with such observations, CXCR4 receptors have been shown to be expressed by hemangioblasts, the earliest common precursor to hematopoietic and endothelial stem cells found in yolk sac blood islands (McLeod et al, 2006) and also by endothelial cells that can be derived from embryonic stem cells (ESCs) in culture (Chen et al, 2007). In the latter case these endothelial cells expressed CXCR4 and migrated towards an SDF-1 gradient.…”
Section: Development Of Non Neuronal Tissuesmentioning
confidence: 66%
“…It forms by vasculogenesis, the differentiation and coalescence of CD39 ϩ angioblasts without proliferation of the angioblasts (McLeod et al, 2006). The vascular markers employed in this study, CD34, CD31, and VWf, were only observed in endothelial cells in formed retinal blood vessels, and not associated with angioblasts.…”
Section: Angiogenesis Involved In Large Choroidal Blood Vessel Develomentioning
confidence: 67%
“…3H-J). CD39 was also present in retinal angioblasts in the avascular embryonic human retina (data not shown) (Chan-Ling et al, 2004;McLeod et al, 2006). VEGFR-2 was also present in cells in inner retina (data not shown) as well as in the sheet of cells under the RPE layer.…”
Section: Temporal and Spatial Relationships Of Vascular Markersmentioning
confidence: 90%
See 2 more Smart Citations